LEGAL PROTECTION OF CHILD VICTIMS OF SEXUAL VIOLENCE AS A CONTINUOUS PROTECTION MEANS (Islamic Law Studies and Psychoanalytic Psychological Theories) - Sulastri, S.; Suharto, S.; Zuhraini, Z.; Nurjanah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2021)
Child protection is a right that must be obtained by children as it has become their rights as stated in the law. Child protection is a guarantee for its part to be upheld because in the constitution there is a guarantee of human rights, especially if you have been a victim of sexual violence. This article aims to find out how legal protection is for Child Victims of Sexual Violence and from the point of view of Islamic law and psychoanalytic psychology theory, which in the end can become sustainable protection. As a country that has various religions, there is Islam which plays a role in providing enlightenment, which is described in Islamic law with various theories. In addition, psychological impacts occur for children, will affect development so it is necessary to know how efforts must be made in terms of Psychoanalytic Psychology theory for this is an ongoing protection given to children as victims of sexual violence. This study uses a qualitative method with subjects AM (14 years) and MT (12 years) who are victims of sexual violence and stepfather perpetrators. The results of the research are: Legal protection must still be obtained, even though there has been a statement of forgiveness by the child as a victim inasmuch as this is clearly influenced by the psychological energy of anxiety caused by him getting wrong treatment from people who must provide protection to him. Islamic law exists so that children get their rights, including protection, education rights, custody rights, housing rights, the right to make choices, the rights of opinion and rights as children who are the hope of the nation.Keywords: Legal Protection, Child Victims Of Sexual Violence, Continuous Protection Means, Islamic Law, Psychoanalytic Psychological Theories